DEVELOPMENT OF MULTIMEDIA WEB-BASED PHYSICS LEARNING TOOLS TO STRENGTHEN STUDENTS’ CHARACTERS - Akhlis, Isa; Aryani, Nila Prasetya (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This research intended to obtain an initial description of students and environment on peace-loving, environmental caring, learning methods, learning materials, and learning media applied in Physics lesson at a high school; moreover, to examine the validity of high school physic learning materials and multimedia web-based physics learning tools in strengthening the students’ characters. The data collection methods employed were (1) documentation, to get the prior data of high school physic materials; (2) observation, to collect the data of students’ initial characters; (3) questionnaire, to obtain the data of learning method, teaching materials, and learning media adopted in the learning process; and (4) validation, to test the developed learning tools’ validity. The results showed that generally, the students have possessed the character of peace-loving, while they rarely owned the environmental caring. In addition, the developed learning tools achieved a good assessment and were declared valid.